Magnetic core material, preparation method thereof and coating inductor

By optimizing the cracking resistance of the core material, the cracking problem of magnetic core material in coated inductors is solved, which improves the reliability and performance of the inductor, simplifies the test process and reduces costs.

CN119541983APending Publication Date: 2025-02-28DONGGUAN SUNLORD ELECTRONICS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411954343.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The core materials in coated inductors are prone to cracking in long-term use or in extreme environments, resulting in degradation of inductor performance or failure.

Method used

By screening and optimizing the Vickers hardness and fracture toughness of the core material, its cracking resistance coefficient Z is within the range of 2≤Z≤8.25, thereby improving the cracking resistance of the core material.

Benefits of technology

It effectively reduces the risk of core materials cracking in coated inductors, improves the reliability and inductance performance of the inductor, simplifies the reliability testing process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215531530000131
    Figure BDA0005215531530000131
  • Figure BDA0005215531530000132
    Figure BDA0005215531530000132
  • Figure BDA0005215531530000141
    Figure BDA0005215531530000141
Patent Text Reader

Abstract

The invention relates to the technical field of electronic components, and particularly discloses a magnetic core material, a preparation method thereof and a coating inductor, the magnetic core material is used in the coating inductor, the magnetic core material has an anti-cracking coefficient Z, the anti-cracking coefficient Z is equal to 0.1 x-0. 5y, x is the Vickers hardness of the magnetic core material, the unit is N / mm < 2 >, y is the fracture toughness of the magnetic core material, the unit is N / mm < 2 >, and Z is greater than or equal to 2 and less than or equal to 8.25. The magnetic core material has excellent anti-cracking performance when being applied to the coating type inductor, the reliability of the coating type inductor using the magnetic core material can be improved, and the risk that the magnetic core material cracks in the using process of the coating type inductor is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic components, and in particular to a magnetic core material and a preparation method thereof, and a coated inductor. Background Art

[0002] As the core component of coated inductors, the core material is mainly composed of sintered magnetic metal oxides. The performance of the core material directly affects the working efficiency of the coated inductor. During the use of coated inductors, under long-term operation or extreme environments, the core material in the coated inductor often cracks, resulting in a decrease in the inductance performance of the coated inductor or even failure. Summary of the invention

[0003] In order to quickly determine a magnetic core material with better anti-cracking performance and improve the inductance performance of a coated inductor, an embodiment of the present invention discloses a magnetic core material and a preparation method thereof, and a coated inductor.

[0004] In a first aspect, an embodiment of the present invention provides a magnetic core material, the magnetic core material is used for a coated inductor, the magnetic core material has an anti-cracking coefficient Z, the anti-cracking coefficient Z=0.1x-0.5y, the x is the Vickers hardness of the magnetic core material, the unit is N / mm 2 , y is the fracture toughness of the magnetic core material, in N / mm, 2≤Z≤8.25.

[0005] As an optional implementation, in an embodiment of the present invention, the value of the anti-cracking coefficient is 3≤Z≤8.

[0006] As an optional implementation, in an embodiment of the present invention, the x is 60N / mm 2 ~100N / mm 2 The y is between 2N / mm and 10N / mm.

[0007] As an optional implementation, in an embodiment of the present invention, the x is 65N / mm 2 ~85N / mm 2 The y is between 3N / mm and 8.5N / mm.

[0008] As an optional implementation, in an embodiment of the present invention, the Vickers hardness of the magnetic core material is obtained by testing according to GB / T 4340.1-2009, and the fracture toughness is obtained by testing according to GB / T 21143-2014.

[0009] As an optional implementation, in an embodiment of the present invention, the magnetic core material is a nickel-zinc ferrite core, and the nickel-zinc ferrite core includes Fe2O3, ZnO and NiO. Taking the total mass of the Fe2O3, the ZnO and the NiO as 100%, the mass percentages of the Fe2O3, the ZnO and the NiO are as follows:

[0010] Fe2O3 60%~70%

[0011] ZnO 10%~15%

[0012] NiO 20%~25%.

[0013] As an optional implementation, in an embodiment of the present invention, the magnetic permeability of the nickel-zinc ferrite core is μ, and μ is greater than or equal to 1000; the loss of the nickel-zinc ferrite core is P, and P is less than or equal to 0.5 W / kg.

[0014] In a second aspect, the present invention provides a method for preparing a magnetic core material.

[0015] A method for preparing a magnetic core material, as mentioned in the first aspect, comprises the following steps:

[0016] The raw materials for preparing the magnetic core material are mixed, pressed into shape and sintered to obtain the magnetic core material.

[0017] As an optional implementation manner, in an embodiment of the present invention, the sintering treatment is performed at 1100° C. to 1250° C. for 1.5 h to 4 h.

[0018] In a third aspect, an embodiment of the present invention provides a coated inductor.

[0019] A coated inductor comprises the magnetic core material as mentioned in the first aspect or the magnetic core material prepared by the preparation method as mentioned in the second aspect.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] An embodiment of the present invention provides a magnetic core material for a coated inductor, wherein the anti-cracking coefficient Z of the magnetic core material is 2 to 8.25, indicating that it has excellent anti-cracking performance when used in coated inductors, and can improve the reliability of coated inductors using the magnetic core material, and effectively reduce the risk of cracking of the magnetic core material during the use of the coated inductor. Among them, the anti-cracking coefficient Z of the magnetic core material is reflected by the Vickers hardness and fracture toughness of the magnetic core material, and the three have a relationship of Z=0.1x-0.5y, and Z is 2 to 8.25. That is to say, in the embodiment of the present application, by screening the magnetic core material whose Vickers hardness and fracture toughness satisfy the above relationship, a magnetic core material with excellent anti-cracking performance can be obtained, so that it can meet the application requirements in coated inductors.

[0022] Different from the prior art, which requires first winding the magnetic core material with a coil and coating it to form a coated inductor, and then conducting a reliability test to determine the cracking performance, the embodiment of the present application can obtain a magnetic core material with excellent cracking resistance by satisfying the above relationship range with the Vickers hardness and fracture toughness of the magnetic core material itself. In this way, the reliability of the magnetic core material in the coated inductor can be confirmed in advance without making the magnetic core material into a coated inductor, which is conducive to timely identification of potential cracking problems, improving the production efficiency and yield of coated inductors, and reducing their production costs.

[0023] In addition, unlike the prior art which requires long-term cycle testing to reflect the reliability of the magnetic core material in the coated inductor, the Vickers hardness and fracture toughness test in the embodiment of the present application is simple, fast, and low-cost. In this way, the present invention can accurately evaluate the anti-cracking performance of the magnetic core material based on whether the Vickers hardness and fracture toughness of the magnetic core material meet the above-mentioned specific relationship, thereby replacing the traditional high-cost reliability test. Therefore, the present invention is of great significance for judging and improving the anti-cracking performance of the magnetic core material used in the coated inductor. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Coated inductors are mainly composed of a magnetic core material, a wire coil wrapped around the outer periphery of the magnetic core material, and a coating material encapsulated on the surface of the wire coil and the magnetic core material. However, the relatively easy cracking of the magnetic core material often leads to a decline in the performance of the coated inductor, affecting the stability of the overall equipment. In order to ensure the reliability of the performance of the coated inductor and to ensure that the core material has good anti-cracking performance during the use of the coated inductor, it is necessary to conduct a variety of reliability tests on the coated inductor, such as high and low temperature reliability tests and mechanical impact reliability tests. However, these test methods are generally time-consuming and costly.

[0026] Take the high and low temperature reliability test as an example. This test simulates the extreme temperature environment that coated inductors may encounter in actual applications. During the test, coated inductors need to cycle between high and low temperatures multiple times, and the performance of coated inductors must be observed and evaluated after each cycle. Since the number of temperature cycles and the performance evaluation after each cycle require time, the entire testing process takes a long time. At the same time, in order to maintain high and low temperature environments and conduct performance evaluations, a lot of resources need to be invested, which increases the cost of testing. Other reliability tests also have similar problems, either requiring a large number of repeated tests on the same indicator, or requiring a cyclic experiment with a long test cycle, or requiring the purchase of expensive test settings, building a simulation test environment, and so on.

[0027] Moreover, if the reliability test results of coated inductors are not satisfactory, not only the core materials need to be scrapped or reprocessed, but also the wire coils and coating materials are wasted. It can be seen that in order to ensure the good reliability of coated inductors, the time-consuming and costly problems are more serious from the raw materials, production to testing of coated inductors.

[0028] Through in-depth analysis and research on the above problems, the embodiments of the present application provide a magnetic core material and a preparation method thereof, and a coated inductor, which solve the above problems by obtaining a magnetic core material with excellent anti-cracking performance.

[0029] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0030] In a first aspect, an embodiment of the present invention provides a magnetic core material.

[0031] A magnetic core material, which is used in a coated inductor, has an anti-cracking coefficient Z, where the anti-cracking coefficient Z=0.1x-0.5y, where x is the Vickers hardness of the magnetic core material, in N / mm 2 , y is the fracture toughness of the core material, in N / mm, 2≤Z≤8.25.

[0032] The inventors found that the anti-cracking coefficient Z of the magnetic core material is 2 to 8.25, indicating that it has excellent anti-cracking performance when used in coated inductors, which can improve the reliability of coated inductors using the magnetic core material and effectively reduce the risk of cracking of the magnetic core material during the use of coated inductors. Among them, the anti-cracking coefficient Z of the magnetic core material is reflected by the Vickers hardness and fracture toughness of the magnetic core material. The three have a relationship of Z=0.1x-0.5y, and Z is 2 to 8.25. In other words, in the embodiment of the present application, by screening the magnetic core materials whose Vickers hardness and fracture toughness satisfy the above relationship, a magnetic core material with excellent anti-cracking performance can be obtained, so that it can meet the application requirements in coated inductors.

[0033] Different from the prior art, which requires first winding the magnetic core material with a coil and coating it to form a coated inductor, and then conducting a reliability test to determine the cracking performance, the embodiment of the present application can obtain a magnetic core material with excellent cracking resistance by satisfying the above relationship range with the Vickers hardness and fracture toughness of the magnetic core material itself. In this way, the reliability of the magnetic core material in the coated inductor can be confirmed in advance without making the magnetic core material into a coated inductor, which is conducive to timely identification of potential cracking problems, improving the production efficiency and yield of coated inductors, and reducing their production costs.

[0034] In addition, unlike the prior art which requires long-term cycle testing to reflect the reliability of the magnetic core material in the coated inductor, the Vickers hardness and fracture toughness test in the embodiment of the present application is simple, fast, and low-cost. In this way, the present invention can accurately evaluate the anti-cracking performance of the magnetic core material based on whether the Vickers hardness and fracture toughness of the magnetic core material meet the above-mentioned specific relationship, thereby replacing the traditional high-cost reliability test. Therefore, the present invention is of great significance for judging and improving the anti-cracking performance of the magnetic core material used in the coated inductor.

[0035] It should be noted that Vickers hardness is a standard for indicating the hardness of a material. The test is performed by pressing a square-conical diamond indenter with a relative angle of 136° into the material surface with a certain load, keeping it for a specified time, measuring the diagonal length of the indentation, and dividing the load value by the surface area of ​​the indentation pit to obtain the hardness value.

[0036] Fracture toughness is the impedance value displayed by the material when unstable fracture occurs, which is used to indicate the ability to resist the unstable extension of macro cracks. The fracture toughness of the present invention is the fracture toughness value (KIC). The fracture toughness is measured by the indentation method.

[0037] The anti-cracking coefficient is used to indicate the anti-cracking performance of the magnetic core material used in the above-mentioned coated inductors. When the anti-cracking coefficient satisfies 2≤Z≤8.25, it indicates that the magnetic core material has excellent anti-cracking performance, and the coated inductor is not prone to the problem of magnetic core material cracking during use, and the reliability is reduced. When the Vickers hardness and fracture toughness of the magnetic core material are less than 2 or greater than 8.25, it indicates that the anti-cracking performance of the magnetic core material is relatively poor, and the coated inductor is prone to the problem of magnetic core material cracking during use, and the reliability is reduced.

[0038] In some embodiments, the anti-cracking coefficient is 3≤Z≤8.

[0039] When the value of z is between 3 and 8, it indicates that the crack resistance of the core material is further improved. This helps to better reduce the risk of cracking of the core material during use of the coated inductor and further improve the reliability of the coated inductor.

[0040] In some embodiments, x is 60 N / mm 2 ~100N / mm 2 , y is between 2N / mm and 10N / mm.

[0041] When the value of z is between 2 and 8.25, and the above given x and y are within a specific range, it is revealed that the core material has a better crack resistance. Compared with the traditional evaluation of crack resistance after the coated inductor is made, the establishment of the Vickers hardness range and fracture toughness range of the core material can more quickly judge the crack resistance of the core material, thereby quickly identifying the risk of cracking of the core material during the use of the coated inductor.

[0042] Moreover, this also means that by adjusting the hardness and fracture toughness of the core material within a specific range, the anti-cracking performance of the core material can be significantly optimized.

[0043] In some embodiments, x is 65 N / mm 2 ~85N / mm 2 y is between 3N / mm and 8.5N / mm.

[0044] By further limiting the range of x and y, the value of z can be made to fall into a more optimal range. This shows that by limiting the hardness and fracture toughness of the core material to this range, the crack resistance of the core material in the coated inductor is further improved.

[0045] In some embodiments, the magnetic core material is a nickel-zinc ferrite core, and the nickel-zinc ferrite core includes Fe2O3, ZnO and NiO. Taking the total mass of Fe2O3, ZnO and NiO as 100%, the mass percentages of Fe2O3, ZnO and NiO are as follows:

[0046] Fe2O3 60%~70%

[0047] ZnO 10%~15%

[0048] NiO 20%~25%.

[0049] Nickel-zinc ferrite core is a core material mainly composed of nickel-zinc ferrite. By adjusting the composition of Fe2O3, ZnO and NiO in the nickel-zinc ferrite core material, the microstructure of the nickel-zinc ferrite core material can be optimized, and the hardness of the nickel-zinc ferrite core material can be improved while reducing the brittleness of the nickel-zinc ferrite core material, so as to further optimize the anti-cracking performance of the nickel-zinc ferrite core material and reduce the risk of anti-cracking of the nickel-zinc ferrite core material in coated inductors.

[0050] In some embodiments, the magnetic permeability of the nickel-zinc ferrite core is μ, μ is greater than or equal to 1000, and the loss of the nickel-zinc ferrite core is P, P is less than or equal to 0.5 W / kg.

[0051] When Fe2O3, ZnO and NiO in the nickel-zinc ferrite core are composed according to the above proportions, it is not only beneficial to take into account the hardness and brittleness of the nickel-zinc ferrite core, but also beneficial to further improve the magnetic permeability of the nickel-zinc ferrite core, reduce the loss of the nickel-zinc ferrite core, and improve the overall performance of the nickel-zinc ferrite core, so as to better improve the overall operating effect of the coated inductor.

[0052] In a second aspect, the present invention provides a method for preparing a magnetic core material.

[0053] A method for preparing a magnetic core material, as mentioned in the first aspect, comprises the following steps:

[0054] The raw materials for preparing the magnetic core material are mixed, pressed into shape and sintered to obtain the magnetic core material.

[0055] The magnetic core material whose Vickers hardness and fracture toughness satisfy a specific relationship can be obtained by the relatively simple preparation method.

[0056] In some embodiments, the sintering process is performed at 1100° C. to 1250° C. for 1.5 h to 4 h.

[0057] By controlling the sintering temperature and time so that the core material can be sintered under specific conditions, it is beneficial to further improve the control of the hardness and brittleness of the core material, and to improve the fracture toughness of the material while improving the Vickers hardness, so as to further improve the anti-cracking performance of the core material, and to improve the reliability of the coated inductor.

[0058] In some embodiments, the preparation of the magnetic core material comprises the following steps:

[0059] The powdered Fe2O3, ZnO and NiO are mixed uniformly to obtain magnetic powder;

[0060] The magnetic core powder, polyvinyl alcohol and silica sol are mixed and pressed, and then pre-fired in an air atmosphere and crushed to obtain pre-fired powder;

[0061] The pre-sintered powder is mixed with glass powder and ball-milled, and then a coupling agent, polyvinyl alcohol and lithium carbonate are added and mixed to form granules, and then pressed to form a magnetic core embryo. The magnetic core embryo is placed in an air atmosphere for secondary sintering to obtain a magnetic core material.

[0062] In a third aspect, an embodiment of the present invention provides a coated inductor.

[0063] A coated inductor comprises the magnetic core material as mentioned in the first aspect or the magnetic core material prepared by the preparation method as mentioned in the second aspect.

[0064] The technical solution of the present invention is further described below in conjunction with more specific embodiments.

[0065] Example 1

[0066] An embodiment of the present invention provides a method for preparing a magnetic core material, comprising the following steps:

[0067] Fe2O3 with an average particle size of 1.8 μm, ZnO with an average particle size of 5 μm, and NiO with an average particle size of 26 μm are mixed to prepare magnetic powder, wherein the total mass of Fe2O3, ZnO, and NiO is 100%, the proportion of Fe2O3 is 60%, the proportion of ZnO is 15%, and the proportion of NiO is 25%;

[0068] The magnetic powder, silicon dioxide particles with an average particle size of 0.5 μm and silica sol are uniformly mixed, wherein the mass ratio of the magnetic powder, silicon dioxide particles and silica sol is 1:0.035:1.2, and the mixed material is pre-calcined at 1100° C. for 3 hours in an air atmosphere, and then crushed to obtain a pre-calcined powder with an average particle size of 12 μm;

[0069] The pre-sintered powder is mixed with glass powder having an average particle size of 4.5 μm and ball-milled to form a mixed powder, wherein the glass powder is composed of SiO2, B2O3 and Al2O3 mixed in a mass ratio of 55:15:30, and the mass ratio of the pre-sintered powder to the glass powder is 1:0.0015;

[0070] The mixed powder, trimethoxysilane, silica particles with an average particle size of 0.5 μm and lithium carbonate with an average particle size of 0.4 μm are mixed and granulated, the mass ratio of the mixed powder, trimethoxysilane, silica particles and lithium carbonate is 1:0.0015:0.035:0.003, and then pressed into shape to obtain a magnetic core embryo, and the magnetic core embryo is placed in an air atmosphere and sintered at 1250°C for 1.5 hours to obtain a magnetic core material.

[0071] Example 2

[0072] An embodiment of the present invention provides a method for preparing a magnetic core material, comprising the following steps:

[0073] Fe2O3 with an average particle size of 1.8 μm, ZnO with an average particle size of 5 μm, and NiO with an average particle size of 26 μm are mixed to prepare magnetic powder, wherein the total mass of Fe2O3, ZnO, and NiO is 100%, the proportion of Fe2O3 is 65%, the proportion of ZnO is 12%, and the proportion of NiO is 23%;

[0074] The magnetic powder, silicon dioxide particles with an average particle size of 0.5 μm and silica sol are uniformly mixed, wherein the mass ratio of the magnetic powder, silicon dioxide particles and silica sol is 1:0.035:1.2, and the mixed material is pre-calcined at 1150° C. for 2.5 hours in an air atmosphere, and then crushed to obtain a pre-calcined powder with an average particle size of 12 μm;

[0075] The pre-sintered powder is mixed with glass powder having an average particle size of 4.5 μm and ball-milled to form a mixed powder, wherein the glass powder is composed of SiO2, B2O3 and Al2O3 mixed in a mass ratio of 55:15:30, and the mass ratio of the pre-sintered powder to the glass powder is 1:0.0015;

[0076] The mixed powder, trimethoxysilane, silica particles with an average particle size of 0.5 μm and lithium carbonate with an average particle size of 0.4 μm are mixed and granulated, the mass ratio of the mixed powder, trimethoxysilane, silica particles and lithium carbonate is 1:0.0015:0.035:0.003, and then pressed into shape to obtain a magnetic core embryo, and the magnetic core embryo is placed in an air atmosphere and sintered at 1250°C for 1.5 hours to obtain a magnetic core material.

[0077] Example 3

[0078] An embodiment of the present invention provides a method for preparing a magnetic core material, comprising the following steps:

[0079] Fe2O3 with an average particle size of 1.8 μm, ZnO with an average particle size of 5 μm, and NiO with an average particle size of 26 μm are mixed to prepare magnetic powder, wherein the total mass of Fe2O3, ZnO, and NiO is 100%, the proportion of Fe2O3 is 70%, the proportion of ZnO is 10%, and the proportion of NiO is 20%;

[0080] The magnetic powder, silicon dioxide particles with an average particle size of 0.5 μm and silica sol are uniformly mixed, wherein the mass ratio of the magnetic powder, silicon dioxide particles and silica sol is 1:0.035:1.2, and the mixed material is pre-calcined at 1200° C. for 4 hours in an air atmosphere, and then crushed to obtain a pre-calcined powder with an average particle size of 12 μm;

[0081] The pre-sintered powder is mixed with glass powder having an average particle size of 4.5 μm and ball-milled to form a mixed powder, wherein the glass powder is composed of SiO2, B2O3 and Al2O3 mixed in a mass ratio of 55:15:30, and the mass ratio of the pre-sintered powder to the glass powder is 1:0.0015;

[0082] The mixed powder, trimethoxysilane, silica particles with an average particle size of 0.5 μm and lithium carbonate with an average particle size of 0.4 μm are mixed and granulated, the mass ratio of the mixed powder, trimethoxysilane, silica particles and lithium carbonate is 1:0.0015:0.035:0.003, and then pressed into shape to obtain a magnetic core embryo, and the magnetic core embryo is placed in an air atmosphere and sintered at 1250°C for 1.5 hours to obtain a magnetic core material.

[0083] Comparative Example 1

[0084] The comparative example of the present invention provides a method for preparing a magnetic core material, comprising the following steps:

[0085] Fe2O3 with an average particle size of 1.8 μm, ZnO with an average particle size of 5 μm, and NiO with an average particle size of 26 μm are mixed to prepare magnetic powder, wherein the total mass of Fe2O3, ZnO, and NiO is 100%, the proportion of Fe2O3 is 72%, the proportion of ZnO is 10%, and the proportion of NiO is 18%;

[0086] The magnetic powder, silicon dioxide particles with an average particle size of 0.5 μm and silica sol are uniformly mixed, wherein the mass ratio of the magnetic powder, silicon dioxide particles and silica sol is 1:0.035:1.2, and the mixed material is pre-calcined at 1100° C. for 3 hours in an air atmosphere, and then crushed to obtain a pre-calcined powder with an average particle size of 12 μm;

[0087] The pre-sintered powder is mixed with glass powder having an average particle size of 4.5 μm and ball-milled to form a mixed powder, wherein the glass powder is composed of SiO2, B2O3 and Al2O3 mixed in a mass ratio of 55:15:30, and the mass ratio of the pre-sintered powder to the glass powder is 1:0.0015;

[0088] The mixed powder, trimethoxysilane, silica particles with an average particle size of 0.5 μm and lithium carbonate with an average particle size of 0.4 μm are mixed and granulated, the mass ratio of the mixed powder, trimethoxysilane, silica particles and lithium carbonate is 1:0.0015:0.035:0.003, and then pressed into shape to obtain a magnetic core embryo, and the magnetic core embryo is placed in an air atmosphere and sintered at 1250°C for 1.5 hours to obtain a magnetic core material.

[0089] Comparative Example 2

[0090] The comparative example of the present invention provides a method for preparing a magnetic core material, comprising the following steps:

[0091] Fe2O3 with an average particle size of 1.8 μm, ZnO with an average particle size of 5 μm, and NiO with an average particle size of 26 μm are mixed to prepare magnetic powder, wherein the total mass of Fe2O3, ZnO, and NiO is 100%, the proportion of Fe2O3 is 58%, the proportion of ZnO is 12%, and the proportion of NiO is 30%;

[0092] The magnetic powder, silicon dioxide particles with an average particle size of 0.5 μm and silica sol are uniformly mixed, wherein the mass ratio of the magnetic powder, silicon dioxide particles and silica sol is 1:0.035:1.2, and the mixed material is pre-calcined at 1100° C. for 3 hours in an air atmosphere, and then crushed to obtain a pre-calcined powder with an average particle size of 12 μm;

[0093] The pre-sintered powder is mixed with glass powder having an average particle size of 4.5 μm and ball-milled to form a mixed powder, wherein the glass powder is composed of SiO2, B2O3 and Al2O3 mixed in a mass ratio of 55:15:30, and the mass ratio of the pre-sintered powder to the glass powder is 1:0.0015;

[0094] The mixed powder, trimethoxysilane, silica particles with an average particle size of 0.5 μm and lithium carbonate with an average particle size of 0.4 μm are mixed and granulated, the mass ratio of the mixed powder, trimethoxysilane, silica particles and lithium carbonate is 1:0.0015:0.035:0.003, and then pressed into shape to obtain a magnetic core embryo, and the magnetic core embryo is placed in an air atmosphere and sintered at 1250°C for 1.5 hours to obtain a magnetic core material.

[0095] Comparative Example 3

[0096] The comparative example of the present invention provides a method for preparing a magnetic core material, comprising the following steps:

[0097] Fe2O3 with an average particle size of 1.8 μm, ZnO with an average particle size of 5 μm, and NiO with an average particle size of 26 μm are mixed to prepare magnetic powder, wherein the total mass of Fe2O3, ZnO, and NiO is 100%, the proportion of Fe2O3 is 60%, the proportion of ZnO is 15%, and the proportion of NiO is 25%;

[0098] The magnetic powder, silicon dioxide particles with an average particle size of 0.5 μm and silica sol are uniformly mixed, wherein the mass ratio of the magnetic powder, silicon dioxide particles and silica sol is 1:0.035:1.2, and the mixed material is pre-calcined at 1100° C. for 3 hours in an air atmosphere, and then crushed to obtain a pre-calcined powder with an average particle size of 12 μm;

[0099] The pre-sintered powder is mixed with glass powder having an average particle size of 4.5 μm and ball-milled to form a mixed powder, wherein the glass powder is composed of SiO2, B2O3 and Al2O3 mixed in a mass ratio of 55:15:30, and the mass ratio of the pre-sintered powder to the glass powder is 1:0.0015;

[0100] The mixed powder, trimethoxysilane, silica particles with an average particle size of 0.5 μm and lithium carbonate with an average particle size of 0.4 μm are mixed and granulated, the mass ratio of the mixed powder, trimethoxysilane, silica particles and lithium carbonate is 1:0.0015:0.035:0.003, and then pressed into shape to obtain a magnetic core embryo, and the magnetic core embryo is placed in an air atmosphere and sintered at 1250°C for 1.5 hours to obtain a magnetic core material.

[0101] Experiment 1

[0102] Vickers hardness and fracture toughness test of magnetic core materials

[0103] According to the preparation method of the magnetic core material provided in the above embodiment and comparative example, a magnetic core material sample is prepared, and a Vickers hardness test is performed on the magnetic core material sample according to the Vickers hardness method. The Vickers hardness of the magnetic core material is obtained by testing according to GB / T4340.1-2009, and the fracture toughness of the magnetic core material is obtained by testing according to GB / T 21143-2014, wherein the calculation formula of the fracture toughness is:

[0104] Fracture toughness value (KIC) = (load P × Young's modulus E of the material) / (crack length C). Where E is the Young's modulus of the material, for example, Si3N4 system is usually 300GPa. The unit of P is kg, the unit of C is mm, and the unit of HV (microhardness) is GPa.

[0105] The anti-cracking coefficient is calculated based on the above test results of Vickers hardness and fracture toughness. The test results of Experiment 1 are shown in Table 1.

[0106] Experiment 2

[0107] 2.1. Core mechanical strength test

[0108] The tests include:

[0109] 2.1.1. Swing folding strength: The magnetic core material samples prepared in the above embodiments and comparative examples were respectively subjected to swing folding strength tests using a material testing machine, wherein the swing folding strength test pressure head is a square pressure head of 0.5 mm × 0.4 mm, and the pressing speed of the pressure head is less than or equal to 10 mm / min. The swing folding strength is recorded in N.

[0110] 2.1.2. Core folding strength: The core folding strength of the magnetic core material samples prepared in the above embodiments and comparative examples was tested by a material testing machine, wherein the core folding strength test punch was a square punch of 0.2 mm × 2 mm, and the pressing speed of the punch was less than or equal to 10 mm / min. The core folding strength was recorded in N.

[0111] 2.2 Reliability test of coated inductors

[0112] First prepare the coated inductor:

[0113] 1. Winding: Wind the copper wire with a conductor diameter of 0.09 mm around the I-shaped magnetic core for 10.75 turns;

[0114] 2. Tinning: Place the wound product in a 400°C tin furnace for tinning, ensuring that the solder evenly covers the ends of the coil and the contact parts with the magnetic core to form a good electrical connection.

[0115] 3. Magnetic glue coating: The magnetic glue is evenly coated in the gap between the coil and the magnetic core. After coating, a curing treatment is performed to solidify the magnetic glue and form a magnetic shielding layer.

[0116] The methods for preparing the magnetic core materials provided in the above embodiments and comparative examples are respectively used to prepare magnetic core material samples as raw materials for preparing magnetic cores of coated inductors, and coated inductor samples are prepared and tested.

[0117] Then conduct the following reliability tests:

[0118] 2.2.1. High and low temperature impact reliability test:

[0119] 77 parallel coated inductor samples were taken and reflow pretreatment was performed three times on these samples to ensure that they reached a stable state before testing;

[0120] The sample is cycled in the temperature range of -40℃ (30min) to +85℃ (30min), and the temperature zone switching time does not exceed 20s, for a total of 100 cycles. After 100 cycles, if the sample still meets the inspection standards, the number of cycles can be increased as appropriate.

[0121] After testing, the samples are inspected and those that meet the following requirements are considered to meet the inspection standards:

[0122] 1. No visible physical damage on the exterior;

[0123] 2. The inductance fluctuation rate before and after the test is within 10%.

[0124] For specific test methods and test standards, refer to Method 107 in MIL-STD-202.

[0125] 2.2.2, Low frequency vibration reliability test:

[0126] Select coated inductor samples and perform three reflow pretreatments to ensure they reach a stable state before testing;

[0127] The sample is soldered to the PCB board and placed in the vibration test equipment. The test frequency is set to 10~55~10Hz, each frequency segment lasts for 1 minute, the amplitude (PP) is 1.524mm, and the test covers vibration in three directions: X, Y, and Z, with vibration in each direction for 2 hours for a total of 6 hours. After the 6-hour vibration experiment, if the sample still meets the inspection standards, the vibration time can be extended as appropriate.

[0128] After testing, the samples are inspected and those that meet the following requirements are considered to meet the inspection standards:

[0129] 1. No visible physical damage on the exterior;

[0130] 2. The inductance fluctuation rate before and after the test is within 10%.

[0131] For specific test methods and test standards, refer to Method 201 in MIL-STD-202.

[0132] The test results of Experiment 2 are shown in Table 2.

[0133] Table 1

[0134]

[0135] Table 2

[0136]

[0137]

[0138] From the comparison of the test results of Examples 1-3 and Comparative Examples 1-3 in Table 2, it can be clearly observed that Examples 1-3 are significantly better than Comparative Examples 1-3 in terms of swing fold strength, core fold strength, high and low temperature impact reliability, and low frequency vibration reliability. This result proves that the magnetic core material used in Examples 1-3 has excellent crack resistance, and can effectively resist cracking during the actual application of coated inductors, thereby significantly improving the overall reliability of coated inductors. Specifically, this high crack resistance means that the coated inductor is not prone to significant changes in inductance due to cracking of the magnetic core material during use, which ensures the stability of the performance of the coated inductor.

[0139] Further combined with the test results in Table 1, the anti-cracking coefficients of the core materials of Examples 1-3 are strictly controlled within the range of 2 to 8.25, while the anti-cracking coefficients of the core materials of Comparative Examples 1-3 are all beyond this range. This data comparison not only verifies the importance of the anti-cracking coefficient within a specific value range (i.e., 2 to 8.25) for improving the anti-cracking ability of the core material, but also directly illustrates that only when the anti-cracking coefficient of the core material meets this condition, the coated inductor using the core material can show higher reliability. In other words, by optimizing the anti-cracking coefficient of the core material so that it falls within the range of 2 to 8.25, we can effectively reduce the risk of failure of the coated inductor due to cracking of the core material during use, which is of great significance for improving the long-term stability and service life of the inductor.

[0140] The magnetic core material and its preparation method, and the coated inductor disclosed in the embodiments of the present invention are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the magnetic core material and its preparation method, the coated inductor and its core concept of the present invention; at the same time, for general technicians in this field, according to the concept of the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A magnetic core material, characterized in that: The magnetic core material is used for a coated inductor, and the magnetic core material has an anti-cracking coefficient Z, wherein the anti-cracking coefficient Z=0.1x-0.5y, and x is the Vickers hardness of the magnetic core material, in N / mm. 2 , y is the fracture toughness of the magnetic core material, in N / mm, 2≤Z≤8.

25.

2. The magnetic core material according to claim 1, characterized in that: The value of the anti-cracking coefficient is 3≤Z≤8.

3. The magnetic core material according to claim 1, characterized in that: The x is 60N / mm 2 ~100N / mm 2 The y is between 2N / mm and 10N / mm.

4. The magnetic core material according to claim 3, characterized in that: The x is 65N / mm 2 ~85N / mm 2 The y is between 3N / mm and 8.5N / mm.

5. The magnetic core material according to any one of claims 1 to 4, characterized in that: The Vickers hardness of the magnetic core material is obtained by testing according to GB / T4340.1-2009, and the fracture toughness is obtained by testing according to GB / T21143-2014.

6. The magnetic core material according to any one of claims 1 to 4, characterized in that: The magnetic core material is a nickel-zinc ferrite core, and the nickel-zinc ferrite core includes Fe2O3, ZnO and NiO. Taking the total mass of the Fe2O3, the ZnO and the NiO as 100%, the mass percentages of the Fe2O3, the ZnO and the NiO are as follows: Fe2O3 60%~70% ZnO 10%~15% NiO 20%~25%.

7. The magnetic core material according to claim 6, characterized in that: The magnetic permeability of the magnetic core material is μ, and μ is greater than or equal to 1000. The loss of the magnetic core material is P, and P is less than or equal to 0.5 W / kg.

8. A method for preparing a magnetic core material, characterized in that: The method for preparing the magnetic core material according to any one of claims 1 to 7 comprises the following steps: The raw materials for preparing the magnetic core material are mixed, pressed into shape and sintered to obtain the magnetic core material.

9. The method for preparing a magnetic core material according to claim 8, characterized in that: The sintering process is carried out at 1100° C. to 1250° C. for 1.5 h to 4 h.

10. A coated inductor, characterized in that: The invention comprises the magnetic core material as described in any one of claims 1 to 7 or the magnetic core material prepared by the preparation method as described in any one of claims 8 to 9.

Citation Information

Cited By

  • Magnetic core material, preparation method therefor, and coated inductor

    WO2026138814A1